The Zadko Telescope: A Southern Hemisphere Telescope for Optical Transient Searches, Multi-Messenger Astronomy and Education - Coward, D.; Todd, Michael; Vaalsta, T.; Laas-Bourez, M.; Klotz, A.; Imerito, A.; Yan, L.; Luckas, P.; Fletcher, A.; Zadnik, Marjan; Burman, R.; Blair, D.; et al. (CSIRO, 2010)
The new 1m f/4 fast-slew Zadko Telescope was installed in June 2008 about 70 km north of Perth, Western Australia. It is the only metre-class optical facility at this southern latitude between the east coast of Australia and SouthAfrica, and can rapidly image optical transients at a longitude notmonitored by other similar facilities.We report on first imaging tests of a pilot programofminor planet searches, and Target of Opportunity observations triggered by the Swift satellite. In 12 months, 6 gamma-ray burst afterglows were detected, with estimated magnitudes; two of them, GRB 090205 (z=4.65) and GRB 090516 (z=4.11), are among the most distant optical transients imaged by an Australian telescope. Many asteroidswere observed in a systematic 3-month search. In September 2009, an automatic telescope control systemwas installed, which will be used to link the facility to a global robotic telescope network; future targets will include fast optical transients triggered by high-energy satellites, radio transient detections, and LIGO gravitational wave candidate events. We also outline the importance of the facility as a potential tool for education, training, and public outreach.